Off Duty (London : Trades Union Congress General Council, 1937)
1937 1937 1930s 12 pages : illustrations Let's write to THE TIMES about it! These Letters were written last year - Have they helped to improve your conditions? NO? - Then we must think of something else. NURSES' HOURS TO THE EDITOR OF THE TIMES Sir. In one of the greatest London voluntary hospitals the nurses have no comfortable room in which to sit when off duty. They either go to their bedrooms (where they are not allowed to smoke) or else spend some of their very scanty pay on buying a seat for the price of tea or coffee in a restaurant. Their holidays and off-duty time are badly organised; it is no uncommon thing for a nurse to be sent off for her summer holiday a two or three days' notice, so that no plans can be made in advance. They are not paid before leaving for their holidaty unless pay-day coincides with their departure. These faults are probably due to the matron's office being run, not be trainee business women, but by nurses with no special qualifications. The nurses are given no extra time off duty to prepare for hospital and State examinations. All such work, including attendance at some of the lectures, comes out of their three hours of freedom. Nurses who have been on night duty are expected to go in the morning straight from the wards to lectures. The food is never varied, unappetizingly served, always tepid, and often badly cooked. A nurse told me that they lived principally on bread and cheese because that alone could not be spoilt. The time allowed for meals is far too short - only half an hour for midday dinner, which may have to include a long walk to and from the dining-room. The root of the trouble seems to lie in the fact that the nursing profession as a whole is controlled by elderly women who, whatever their former services to hospital work, are completely out of touch with modern life and the requirements of youth. When they first took up their [overlaid text - obscured] If the public can pay, [obscured text] opportunity. The Hospital [obscured text] Children is being rebuilt and it is not too late to plan increased accommodation for nurses. Not only would the nurses benefit but the patients would receive better nursing, and, moreover, a much-needed reform in the conditions of the nursing profession would receive a valuable stimulus. Your obedient servant, L. E. BARRINGTON-WARD 85 Harley Street, W. 1. Jan 18 TO THE EDITOR Sir. - With reference to the hours worked by nurses in voluntary hospitals, it may be of interest to your readers to know that at one of the largest of these in London the nurses are on night duty, [obscured] working from 9.20 p.m. till 7.20 a.m., are expected twice weekly to spend the hour from 9 a.m. to 10 a.m. attending a lecture for their qualifying examination. If they fail to do so, disciplinary action is taken. I am, &c., EX-PROBATIONER. [obscured text] be said that no section of ind[obscured] imposes such hours on the labour employed and even 48 hours a week is deemed excessive in most trades. I doubt whether a continuous shift of 6½ hours without a break is worked anywhere except in a hospital. No doubt conditions were even worse years ago, and it may be that present-day matrons and sisters-in-charge see little reason why [obscured] should have less severe training than they experienced themselves. The public take the services they obtain at the hospitals for granted and no change is likely to take place until the present shortage of probationers becomes more [obscured] and the hospitals are forced to make the profession more attractive. No one questions the great work done by hospitals in the public interest, but need it be done so greatly at the expense of the nurse? Yours faithfully, PROBATIONER'S FATHER As the mother of a probation[obscured] just broke down after eight m[obscured] one of the largest voluntary ho[obscured] done I write to criticize the [obscured] "F.R.C.S." that "it is not because [obscured] work is too hard or too long [obscured] and junior nurses break down. Can probationers work for 70 hours a week in the wards, on their feet practically the whole time and sometimes for six hours on end with only [obscured] minutes' break? At the hospital where [obscured] at 6.30 and do not have supper till [obscured] in the wards begins at 7 a.m. [obscured] OVERWORKING OF NURSES TO THE EDITOR OF THE TIMES Sir.— Although my organization is not directly concerned with general nurses, I have nearly 30 years' connexion with the nursing service, acquired considerable knowledge of the grievances which nurses labour under. Apart altogether from the admitted grievance of unduly long hours of labour, the general nursing service is afflicted with a host of absurd and petty regulations which would not tolerated for an instant in any other profession or, indeed, in other branches of the nursing service. For instance, I know of general hospitals where restrictions are imposed of the following nature, not all at one hospital of course, but they indicate the type of mind which is placed in control of the nurses' [obscured] (a) Nurses forbidden to laugh in the classroom (this is not uncommon). Sometime [obscured] are appointed, one to each table, to see that the heinous crime of laughter is not committed. (b) In some hospitals a junior nurse is not permitted to pass a senior nurse in a corridor. The fact that the junior may be in a hurry and the senior dawdling makes no difference. (c) The food is generally inadequate and frequently badly cooked. (d) Many hospitals' standard allowance of butter is one ounce per day per nurse for all [obscured] regulations regarding leave are [obscured] THE EDITOR OF THE TIMES [obscured] our correspondent, Ex-Probation[obscured] understates the case. I know persons [obscured] of the largest of the London hospitals [obscured] schools, where the night nurses are on duty in the wards from 8 p.m. till 8.30 a.m., really working more or less hard all night. [obscured] not a case of just sitting by sleeping patients, they are then obliged to attend lectures of an hour's duration always twice in the week and sometimes as often as four times. Some of the lectures are given by the medical staff, and these are usually in the late afternoon. When this happens the nurses have to ge up earlier from their sleep in order to attend them. Much has been said about nurses' long hours, but nothing done, and these endless examinations add greatly to the toil and strain of their lives. I am, &c., TRAINED NURSE. 292/54.73/2/2